STRATEGI PENGEMBANGAN OBJEK WISATA BANTOROYO - Yuliani, Rozi; Abdi, Moch. (Ensiklopedia of Journal, 2024)
The data collection method is carried out by means of documentation from various secondary sources, including; news in newspapers and mass media, journals and books to look for concepts and theories that are closely related to the problems studied. This research aims to determine opportunities for object development tourism as well as to find out strategies that can be used by managers in developing the Banto Royo tourist attraction which is located in Agam Regency, West Sumatra. The type of research used in this research is descriptive qualitative using the SWOT analysis method to analyze systematically and see the extent to which tourist attraction development strategies are implemented in increasing interest in visits based on strengths, weaknesses, opportunities and threats. The main strategy produced is to make the best use of natural beauty with exotic views to attract the attention of local people, domestic and foreign visitors as well as utilizing local workers to explore a combination of natural and artificial potential to increase the number of visits. Apart from that, it provides restaurants, accommodation and other adequate facilities for domestic and foreign visitors so that visitors feel at home for a long time staying in the Banto Royo tourist attraction area. Apart from that, providing adequate transportation to and during the Banto Royo tourist attraction so that it becomes an easy destination for visitors. So in the IE matrix it is illustrated that the Banto Royo tourist attraction is currently in a growth position (concentration through horizontal integration or stability), namely growth or development, which is an incentive strategy such as market penetration, market development and forward development and product development or an integrated strategy such as backward integration and Horizontal IntegrationKeywords: Strategy, development, tourist attractions, strengths, weaknesses, opportunities, threats